Investigation on the structural, mechanical and in vitro biocompatibility features of CaZr4(PO4)6 influenced by Zn2+ substitutions. Issue 4 (14th October 2019) - Kumar, Manish; Vasanthavel, Subramaniyan; K. Khan, Mohd. Imran; Dhayalan, Arunkumar; Kannan, Sanjeevi
Abstract: The present study explores the possibility of Zn 2+ substituted calcium zirconium phosphate [CaZr4 (PO4 )6 ] as a potential replacement for the existing materials in load bearing orthopedic applications. Pure CaZr4 (PO4 )6 ) and wide range of Zn 2+ substitutions in CaZr4 (PO4 )6 have been synthesized through citrate assisted sol–gel technique. The characterization results confirmed the extraordinary structural stability displayed by CaZr4 (PO4 )6 until 1, 550°C. Further, the flexibility of CaZr4 (PO4 )6 lattice to accommodate 40 mol% of Zn 2+ has been determined. The microstructures of CaZr4 (PO4 )6 and Zn 2+ substituted CaZr4 (PO4 )6 demonstrated irregular sized grains and cracks alongside the negligence to obtain definite grain boundaries. This has been reflected in the moderate mechanical properties of the investigated specimen; nevertheless, Zn 2+ substituted CaZr4 (PO4 )6 displayed enhanced mechanical stability. Further, in vitro tests signified the remarkable biocompatibility and alkaline phosphatase activity of Zn 2+ substituted CaZr4 (PO4 )6 .